Applying and employing the anticipation technique in the novel The Well (Journal of Human Sciences, 2025)
The research aims to explore how the technique of anticipation is applied and employed in the novel Al-Bawr, and its importance lies in its position and scope. This importance increases if necessary and if the need arises, which is the nature of my study, through which I seek to reveal the elements of temporal structure and how they work within the text of the novel Al-Bair. This research relies on a descriptive approach based on analysis. The temporal paradox is a comparison of the system of events, as well as their order or the time segments in the narrative discourse. The change in the temporal order of the story was due to a return to past events or because of anticipating events in the narrative before they occurred in the story's timeline. The temporal paradox appeared to be either a flashback to previous events or an anticipation of subsequent events. Both anticipation and flashbacks have a range and breadth, the length of which is determined by the moment when the narrative stops in the present to return to past events or anticipate subsequent events. The breadth is determined by the space that the anticipation or flashback occupies within the novel. The most important findings of the research were that flashbacks and flash-forwards run in parallel in the first stage of The Well, with frequent flashbacks to the past and rapid flash-forwards, unlike the flashbacks, which are more consistent in terms of narrative and linking events in the novel than the flash-forwards. We find that most of the flash-forwards used by Al-Koni are external flash-forwards of two types: introductory and declarative, followed by internal and supplementary flash-forwards, but to a very limited extent. These flash-forwards clarify events that begin at the beginning of the novel.